Legal framework of Directors' Duties in OHADA Law (Senegal) - Niang, Oumar (International Journal of Business, Economics and Management Works, 2017)
This article is aimed to study the legal framework of directors’ duties in Ohada law. The Organization for the Harmonization of Business Laws (OHADA),is a supranational system of business laws that, as implemented in Senegal is trying to regulate all the core businesses.Ohada displays two level of mixing.Firstly,Ohada Law is supranational, it becomes part of the internal law of each state member but still remains supranational characteristics.Secondly,Ohada being at least partially French-inspired, we can  understand that the most of the countries which adopted Ohada Laws are French-speaking. The duties of Directors in Senegal are regulated mainly by the uniform companies’ act which is part of the Ohada law. It should be noted that before the adoption of Ohada, company law was governed by the code of civil obligations and in its fourth part. For companies listed on the RSE, they must comply both with the general regulations of the BRVM and with the provisions of the Uniform Companies Act concerning publicly traded companies. This article aims to illuminate the lanterns on the question of the duties of directors in Ohada law, during my research I have observed that subjects such as corporate governance in general and the duties of directors in Ohada are left stranded by most researchers. This is why this topic has an interest in reabsorbing this gap insofar as the legal framework of the duties of directors often mentions many questions because of the lack of loyalty and diligence of certain directors.
Keywords: Company law; Corporate; Directors Duties; Governance; Senegal